The impact of conjugation strategies and linker density on the performance of the Spermine-AcDex nanoparticle-splenocyte conjugate - Su, Yuchen; Cheng, Ruoyu; Du, Bowei; Soliman, Mai O.; Zhang, Hongbo; Wang, Shiqi (Royal Society of Chemistry, 2026)
A common approach in living medicine engineering is modifying cell surfaces with nanomedicines to form nanoparticle-cell conjugates. Despite various available strategies, limited research has examined how conjugation strategies affect the efficiency and stability of the delivery systems. Herein, we prepared polymeric nanoparticles (NPs) with protein payloads and modified them with different linkers. These NPs were conjugated to primary splenocytes using either covalent or electrostatic interactions, followed by flow cytometry analysis to evaluate the conjugating efficiency and stability. The results demonstrated that electrostatic interactions were more effective in achieving conjugation, whereas covalent interactions provided greater stability. Furthermore, the linker density on the nanoparticle surface also affected the stability. After three days of in vitro culture, NPs with fewer linkers were predominantly internalized by the splenocytes, whereas those with more linkers partially remained on the cell surface. Overall, this study provides fundamental insights into nanoparticle-cell conjugation, thereby contributing to living medicine design and engineering for therapeutic applications.